Sequence analysis and characterization of the mobilization region of a broad-host-range plasmid, pTF-FC2, isolated from Thiobacillus ferrooxidans. - Rohrer, J (1992)
The nucleotide sequence of a 5,317-bp fragment which includes the region required for mobilization of broad-host-range plasmid pTF-FC2 was determined. A region of approximately 3.5 kb was required for plasmid mobilization, and oriT was localized on a 138-bp fragment. Polypeptides which corresponded in size and location to several of the open reading frames were detected in an in vitro transcription-translation system. Three open reading frames essential for plasmid mobilization and two which affect the mobilization frequency were identified. There was a distinct similarity in the sizes, amino acid sequences, and locations of the proteins from the mobilization region of pTF-FC2 and the Tra1 region of IncP plasmid RP4. Similarity in the structures and sequences of the oriT regions was also apparent. A sequence with 37-of-38-bp homology to the inverted repeated sequences of Tn21 and an open reading frame with strong homology to the MerR regulatory protein was identified outside of the region required for mobilization.